2017
DOI: 10.1021/acs.jpcc.6b12811
|View full text |Cite
|
Sign up to set email alerts
|

Spectral Anomaly in Raman Scattering from p-Type Silicon Nanowires

Abstract: An anomalous nature of Raman spectral asymmetry has been reported here from silicon nanowires (SiNWs) prepared from a heavily doped p-type Si wafer using a metal induced etching technique. Raman spectra of SiNWs prepared from two p-type Si wafers with different doping levels show different behaviors in terms of asymmetry as characterized by the asymmetry ratio. The SiNWs prepared from high doped p-type wafer show an anomaly in asymmetry in addition to the red shift and broadening of the Raman line shape due to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 40 publications
2
38
0
Order By: Relevance
“…MACE formation of SiNW arrays on highly boron‐doped c‐Si substrates leads to the narrowing of nanowire diameter and additional nanowire porosity that results in a distortion of the lower wavenumber side of Fano‐resonance line. [ 32,33,35,36 ] Note that in this case, the observed distortions in Raman spectra correspond to theoretical considerations that phonon confinement reveals itself in the structures with a diameter less that 10–20 nm. [ 23–29,31–34 ] We do not observe any maximum red shift within the chosen spectral resolution or a broader half‐width at the lower wavenumber side of the Raman spectra of as‐prepared and thermally annealed SiNWs (Figure 2a) as could be expected for small‐diameter nanowires.…”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…MACE formation of SiNW arrays on highly boron‐doped c‐Si substrates leads to the narrowing of nanowire diameter and additional nanowire porosity that results in a distortion of the lower wavenumber side of Fano‐resonance line. [ 32,33,35,36 ] Note that in this case, the observed distortions in Raman spectra correspond to theoretical considerations that phonon confinement reveals itself in the structures with a diameter less that 10–20 nm. [ 23–29,31–34 ] We do not observe any maximum red shift within the chosen spectral resolution or a broader half‐width at the lower wavenumber side of the Raman spectra of as‐prepared and thermally annealed SiNWs (Figure 2a) as could be expected for small‐diameter nanowires.…”
Section: Resultssupporting
confidence: 66%
“…Because the Raman line shape can be modified by phonon confinement, [ 22–36 ] one should be scrupulous about the possible impact of phonon confinement to the estimations of the FCC concentration in SiNWs. MACE formation of SiNW arrays on highly boron‐doped c‐Si substrates leads to the narrowing of nanowire diameter and additional nanowire porosity that results in a distortion of the lower wavenumber side of Fano‐resonance line.…”
Section: Resultsmentioning
confidence: 99%
“…In defect-free crystalline semiconductor (bulk) materials one expects perfect symmetry. Asymmetry increases with decreasing crystallite size and is most prominent when size is smaller than Bohr excitation radius ~7.2nm of CeO2 [28,30,31]. Since with reduction of size and dimension an increasing volume of reciprocal space is involved which leads to participation of phonons of other than zone boundary [28].…”
Section: Resultsmentioning
confidence: 99%
“…Besides certain disadvantages, the PCM has been used as the most widely used formulation when it comes to interpretation of the Raman scattering results obtained from low dimensional semiconductors especially elemental ones. In recent attempts to rectify the shortcomings of the PCM, Jia et al [21] have been reported in the previous literature [22][23][24]. In order to confirms the wire like structures formed after etching, transmission electron microscopy (TEM) was carried out using TEM-Gatan model 636MA.…”
Section: Introductionmentioning
confidence: 99%
“…For comparison, Raman line-shape obtained using well-established PCM[13,16,17,23,30], as represented Raman line-shapes theoretically generated using phonon confinement model Eq. 2 for different SiNSs.…”
mentioning
confidence: 99%